Dental Education - Dumancic, Jelena; Brzak, Božana Lončar (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The dental curriculum is like a living organism-it has developed through time, manifesting regional, cultural, and scientific heritage, and reflecting modern trends. The undergraduate dental curriculum is periodically rebuilt to ensure the harmonization of higher education systems between countries, especially in Europe. Structure, content, learning, and assessment in undergraduate and postgraduate dental education and auxiliary dental personnel training are shaped based on professional consensus. Constant updates on recent technological innovations and evidence-based best practice are necessary.In modern times, ethical issues are raised more than ever. Can we teach our students how to be dedicated health professionals and manage a successful practice at the same time? Does the commercialization of our profession also affect the dental curriculum today?The COVID-19 pandemic has imposed new challenges, moving us from lecture rooms and clinics to an online environment.This Special Issue is dedicated to developing the understanding of dental education.